Validating psychometric properties of dual-continua models for university student mental health assessment - Aziz, Rahmat; Mangestuti, Retno (Intelektual Pustaka Media Utama, 2025)
This study rigorously evaluates a mental health assessment tool for college students, grounded in the dual-continua model, which uniquely captures both positive (psychological well-being) and negative (psychological distress) mental health dimensions. Employing a sample of 312 students evenly split by gender, the research meticulously tested the tool's reliability and construct validity. Reliability was confirmed through a robust Cronbach's Alpha of .807, indicating consistency in responses. Construct validity was assessed via confirmatory factor analysis, affirming the tool's capacity to accurately measure the intended constructs with well-being and distress components scoring .828 and .875, respectively. This validation process underscores the instrument's precision and significant contribution to mental health research by providing a nuanced understanding of student mental health through dual-continua models. The findings offer a refined resource for mental health professionals and universities, facilitating the development of targeted interventions. However, the study acknowledges limitations, including its cross-sectional design and the need for further validation across diverse student populations, to ensure the tool's broad applicability and effectiveness in varied contexts.